The Employee Performance Management of the Regional Technical Implementation Unit (UPTD) of the Animal Health and Veterinary Public Health Center of Seruyan Regency in Improving Public Services. - Amirulah, Suriyadi; Rahmat, Widya (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
This research aims to analyze the quality of animal health service management at the Regional Technical Implementation Unit (UPTD) Animal Health Center of Seruyan Regency using the POAC (Planning, Organizing, Actuating, Controlling) management approach. Conducted from June 1 to September 1, 2024, this study employs a qualitative method with descriptive analysis. Data were collected through literature reviews, direct observations, and interviews with staff and management involved in the service delivery process. The findings reveal that the service planning at the UPTD Animal Health Center and Veterinary Public Health has not effectively engaged farmers, which has resulted in a disconnect between the programs offered and the actual needs of the farming community. Although the internal organization of the center is assessed as practical, the accessibility of services for farmers residing in remote areas remains a significant concern that requires attention. The execution of veterinary health services showcases the competence and skills of health workers. However, there are notable deficiencies in communication and the availability of information that hinder effective service delivery. Furthermore, the existing control system does not adequately accommodate user feedback, highlighting an urgent need for enhanced communication channels. Overall, this research aims to provide actionable recommendations to improve the quality of veterinary health services in Seruyan Regency, ultimately fostering a more responsive and user-centered service environment. The insights gained from this study will contribute to the ongoing efforts to align veterinary health services with the community's needs, ensuring better health outcomes for livestock and the farming population.